DAMPAK PANDEMI COVID-19 TERHADAP MANAJEMEN SEKOLAH MINGGU KOREA DI INDONESIA UNTUK PENGINTEGRASIAN PEMBELAJARAN IMAN [THE IMPACT OF THE COVID-19 PANDEMIC ON THE MANAGEMENT OF FAITH-LEARNING INTEGRATION OF KOREAN SUNDAY SCHOOL IN INDONESIA] - Choi, Chi Hyun; Purba, John Tampil; Sudibjo, Niko; Pramono, Rudy (Universitas Pelita Harapan, 2021)
This research is a case study that analyzes the problem of the Faith-Learning Integration management process for the Korean Sunday School “Y” in Indonesia during the COVID-19 pandemic. In this research, data collection was carried out with 5 informants, 58 questionnaires from respondents consisting of students, parents and teachers as well as recordings of student activity results. From the results of this study, it can be seen that there are several obstacles experienced by students, teachers and parents in the Faith-Learning Integration management process. First, students are not satisfied with centering on video learning platforms because there is no interaction between teachers, students and their friends so it needs to be changed from a one-way platform, such as video to an interactive platform between students and teachers such as Zoom or Google Classroom, etc. In addition, students from parents of other religions do not get support and attention from their parents to carry out Faith-Learning Integration with Work From Home (WFH) so that Faith-Learning Integration activities stop. Second, teachers' technical skills are very limited, so interactive online classroom training is required. Third, parents feel burdened and stressed when they have to give examples of faith, morals and good discipline to children in Faith-Learning Integration during WFH. The last obstacle, the 5 dimensions of the Faith-Learning Integration are not tightly integrated with each other so they do not run in harmony. The dimensions of Leitourgia and Didache were implemented well, while Kerygma, Koinonia, and Diakonia were not carried out well due to social distancing obstacles. For this reason, it is recommended that